AB0187 Increased Serum TIE-2 Level in Systemic Lupus Erythematosus Patients and Related Factors. (9th June 2015) - Pamuk, O.N.; Pamuk, G.E.; Gedik, M.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multisystem, chronic inflammatory disease. The activation of endothelial cells determines the initiation, localisation and spread of inflammatory disease. Central nervous system (CNS) involvement in SLE is a life-threating manifestation of disease and it might be related to endothelial injury or thrombosis. Neurofilament (NF) proteins have been shown to be promising biomarkers for monitoring and predicting disease progression for different neurologic disorders. Objectives: In this study, we evaluated biomarkers related to endothelial injury, angiogenesis (tyrosine-kinase with Ig-like and epidermal growth factor-like domain 2, Tie-2) and NF level. In addition, we investigated the association between this parameters and clinical findings in our SLE patients. Methods: Age-and-sex matched 60 SLE patients (56 females, 4 males, mean age: 39.5±11.5 years) and 34 apparently healthy subjects (29 females, 5 males, mean age: 38.2±10.9 years) were included into the study. The demographic, clinical features, major organ involvements - including that of the CNS- and laboratory data of SLE patients were recorded from medical charts. Plasma Tie-2 and neurofilament level were evaluated by ELISA method. SLE disease activity index (SLEDAI) score was calculated at the time of study. NF level was converted to its log level, because the distribution of its level was not normal. Results: Tie-2 level was significantly lower in SLE patients than in healthy controls (19.03±11.9 pg/ml vs. 31.3±15.1 pg/ml, p=0.001). Neurofilamentin level was similar in SLE patients and controls (median: 5.08 (range: 3.09-6.35) pg/ml vs. 5.12 (3.08-5.7) pg/ml, p>0.05). Serum Tie-2 level in SLE patients with major organ involvement was significantly lower than in patients without major organ involvement (13.6±7.8 vs. 20.5±12.4 pg/ml, p=0.05). In the healthy control group, serum Tie-2 level correlated significantly with NF level (r=-0.66, p=0.003). In the SLE group, these parameters did not seem to correlate with each other. Conclusions: Serum Tie-2 level in SLE patients was significantly lower. Decreased Tie-2 level may be related to major organ involvement in SLE. Disclosure of Interest: None declared